2006
DOI: 10.1152/ajprenal.00360.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of blood pressure and renal function in chromosome 5 congenic strains of Dahl S rats

Abstract: The present study examined whether transfer of overlapping regions of chromosome 5 that include (4A ϩ ) or exclude the cytochrome P-450 (CYP) 4A genes from the Lewis rat alters the renal production of 20-hydroxyeicosatetraenoic acid (20-HETE) and/or the development of hypertension in congenic strains of Dahl salt-sensitive (S) rats. The expression of CYP4A protein and the production of 20-HETE in the renal outer medulla was greater in the 4A ϩ congenic strain than the levels seen in S rats or in overlapping co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 31 publications
6
33
0
Order By: Relevance
“…The S.L(5)ϫ6ϫ9 containing L alleles from 116.6 Mb to 134.9 Mb did not result in differential expression of the Cyp4a genes compared with the S rat. These data suggest that genetic factors within 116.6 to 134.9 Mb of RNO5 are not responsible for the observed changes in Cyp4a genes reported by Roman et al, 58 thus lending further support to the view that deficiency of renal formation of 20-HETE contributing to increased BP may be because of functional polymorphisms within the Cyp genes in rats 58 and in humans. 59 …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The S.L(5)ϫ6ϫ9 containing L alleles from 116.6 Mb to 134.9 Mb did not result in differential expression of the Cyp4a genes compared with the S rat. These data suggest that genetic factors within 116.6 to 134.9 Mb of RNO5 are not responsible for the observed changes in Cyp4a genes reported by Roman et al, 58 thus lending further support to the view that deficiency of renal formation of 20-HETE contributing to increased BP may be because of functional polymorphisms within the Cyp genes in rats 58 and in humans. 59 …”
Section: Discussionsupporting
confidence: 57%
“…Roman et al 58 have recently provided evidence for the involvement of a genomic segment on RNO5 encompassing a family of Cyp4a genes in controlling BP of the S rat. Their data suggest that there may be additional QTLs on RNO5, which operate independent of the QTLs reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…5A). Moreover, in previous studies, we reported that blockade of the synthesis of 20-HETE has no additional effect on MAP in SS rats (28,41).…”
Section: Discussionmentioning
confidence: 72%
“…Chronic blockade of the formation of 20-HETE with HET0016 reversed the antihypertensive and renoprotective effects seen in the SS.5 BN consomic strain. In contrast, we have previously demonstrated the chronic inhibition of 20-HETE has no effect on either arterial pressure (28,41) or the degree of proteinuria and renal injury in SS rats (41). The mechanism for an increase in Pgc in SS rats fed a HS diet remains to be determined.…”
Section: Discussionmentioning
confidence: 77%
“…25 Congenic Dahl-S strains harboring the entire region of chromosome 5 that contains the CYP4A genes from Lewis rats exhibit restored synthesis of outer medullary CYP4A protein and 20-HETE and have blunted blood pressure responses to salt and reduced proteinuria compared with Dahl-S strains. 11 However, experiments with different overlapping sections of the transferred chromosome raised the possibility that the CYP4A3 and A8 genes, not A1 and A2, may be responsible for the effect of retrogressing the entire region into the congenic strains. 26 In our early experiments, we measured 20-HETE in subjects with salt-sensitive hypertension in the expectation that urinary excretion might be reduced, analogous to decreased synthesis of the compound in Dahl-S kidney.…”
Section: Discussionmentioning
confidence: 99%